Preliminary results of colostrum quality and passive immunity transfer in calves under tropical conditions - A. E. Guerrero-Pincay; S. A. Guamán-Rivera; C. D. Guilcapi-Carrillo; A. D. Feijoo-Leon; L. A. Moreira-García; J. Llivi-Marcatoma; C. O. Guerra Flores; A. F. Inca Falconí; B. R. Vaca Barahona; V. F. Noboa Silva (Brazilian Journal of Biology)
Abstract Inadequate management of livestock practices causes low colostrum quality and failure in passive transfer of immunity in calves, which increases mortality and production costs for farmers. Therefore, a study has been conducted in order to determine the effectiveness of passive transfer of immunity in the province of Orellana, Amazonian Ecuador. Subsequently, 50 mL of colostrum was collected aseptically from a total of 32 cows before 4 hours postpartum, while blood was extracted from the jugular vein of the calves at 24 h, followed at 7, 15 and 21 days in order to determine total serum proteins. The data were analyzed using a linear mixed model in SAS for repeated measures. According to the results, no differences were observed in the chemical composition of colostrum by breed effect (P = 0.23), age cow and at birth (P = 0.30 to 0.98). Some 67% of the analyzed colostrums contained above 24 degrees Brix%, being classified as high quality. On the contrary, the total serum proteins varied by breed effect (P = 0.03) and by the age and number of births of the cow (P = 0.04 to 0.001), although the sex effect only indicated a statistical tendency (P = 0.07). Consequently, we realized that 60% of the total calves sampled at 24 hours received an effective passive transfer of immunity. Conclusively, the total serum proteins marked differences that could be conditioned by the feed, animal biotype and age of the animal. Therefore, in this pioneer study in Ecuador, an effective transfer of immunity of over 60%, with ≥ 5.5 g/dL has been obtained, which should be studied in more depth in order to determine risk factors under tropical conditions, being most likely of some decisive influence.